Por uma construção relacional da paz: a intersubjetividade na transformação de conflitos de John Paul Lederach - Facchini, Julia (2020)
This dissertation aims to explore the analytical treatment that John Paul Lederach gives to intersubjective elements in his theoretical and practical proposal of conflict transformation. To this end, we first seek to systematize the relational approaches that precede and provide theoretical and conceptual basis for the author's writing. Then we analytically delineate the conflict transformation and its developments to the peacebuilding practice. Finally, we investigate emotions, perceptions and feelings as social forces, as well as the practical approach to treat them in conflicting contexts suggested by the author, which revolves around the idea of reconciliation. With this theoretical effort, we intend not only to explore new perspectives on the debates that address the issues of recognition in conflict resolution and peace studies, but also to disseminate Lederach's ideas, so relevant to current times, in Brazilian academic spaces.